Optimal monetary policy in an estimated DSGE for the euro area - Stéphane Adjemian; Matthieu Darracq Pariès; Stéphane Moyen (European Central Bank (ECB), 2007)
The objective of this paper is to examine the main features of optimal monetary policy within a micro-founded macroeconometric framework. First, using Bayesian techniques, we estimate a medium scale closed economy DSGE for the euro area. Then, we study the properties of the Ramsey allocation through impulse response, variance decomposition and counterfactual analysis. In particular, we show that, controlling for the zero lower bound constraint, does not seem to limit the stabilization properties of optimal monetary policy. the Ramsey allocation reasonably well. Such optimal simple operational rules seem to react specifically to nominal wage inflation. Overall, the Ramsey policy together with its simple rule approximations seem to deliver consistent policy messages and may constitute some useful normative benchmarks within medium to large scale estimated DSGE framework. prove the economic micro-foundation and the econometric identification of the structural disturbances. We also present simple monetary policy rules which can “approximate” and implement However, this normative analysis based on estimated models reinforces the need to improve the economic micro-foundation and the econometric identification of the structural disburbances.
Keywords: E4; E5; 330; Bayesian estimation; DSGE Models; monetary policy; Welfare calculations; Geldpolitik; Dynamisches Gleichgewicht; Eurozone; Theorie